Uprighting Impacted Mandibular Second Molar Using a Skeletal Anchorage: A Case Report - Federica Altieri; Rosanna Guarnieri; Martina Mezio; Gabriella Padalino; Angela Cipollone; Ersilia Barbato; Michele Cassetta (MDPI AG, 2020)
The aim of this case report is to present an innovative combined orthodontic-surgical technique to disimpact mandibular second molar (MM2) using an orthodontic miniscrew and an elastic chain. The impact on the Oral health-related quality of life (OHRQoL) was also evaluated. Using the present techinique, it is possible to expose the impacted tooth, insert a self-drilling miniscrew in the retromolar area, and remove the bud of third mandibular molar. At the same time the orthodontic force is applied with the use of an elastomeric chain that connects the head of miniscrew and vestibular and oral buttons bonded on MM2. A close traction is performed for the whole treatment time without the reactivation of the elastic force. The use of skeletal anchorage allowed the disimpaction of impacted MM2 in a short treatment time (about three months) avoiding the typical biomechanical side effects of traditional orthodontic appliance and increasing the effectiveness of the treatment. Further studies are necessary to evaluate the real advantages and disadvantages of this combined orthodontic-surgical approach.